2020
DOI: 10.33180/infmidem2020.304
|View full text |Cite
|
Sign up to set email alerts
|

Novel Electronically Tunable Biquadratic Mixed- Mode Universal Filter Capable of Operating in MISO and SIMO Configurations

Abstract: In this paper, a novel electronically tunable biquadratic universal mixed-mode filter is presented. The filter is based on extra X current conveyor transconductance amplifier (EXCCTA), recently introduced by authors. The proposed filter employs two EXCCTAs, two capacitors, a switch, and four resistors. The filter can work in both multi-input-single-output (MISO) and single-input-multi-output (SIMO) configurations without change in its structure. The filter provides all five responses in voltage-mode (VM), curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The design of mixed-mode universal filters that can provide low-pass (LP), high-pass (HP), band-pass (BP), band-reject (BR), and all-pass (AP) filter responses in CM, VM, TAM, and TIM modes of operation are needed for the mixed signals system architecture [1,2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The popular analog building blocks (ABBs) that are used in the design of active filters include operational transconductance amplifier (OTA) [5], second-generation current conveyor (CCII) [6], differential voltage current conveyor (DVCC) [16], extra current conveyor transconductance amplifier (EXCCTA) [21], differential difference current conveyor (DDCCII) [18], fully differential current conveyor (FDCCII) [15], current differencing buffer amplifier (CDBA) [3], etc. The voltage differencing buffered amplifier (VDBA) is another popular ABB that is very simple in design and versatile in realizing numerous applications [3,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The design of mixed-mode universal filters that can provide low-pass (LP), high-pass (HP), band-pass (BP), band-reject (BR), and all-pass (AP) filter responses in CM, VM, TAM, and TIM modes of operation are needed for the mixed signals system architecture [1,2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The popular analog building blocks (ABBs) that are used in the design of active filters include operational transconductance amplifier (OTA) [5], second-generation current conveyor (CCII) [6], differential voltage current conveyor (DVCC) [16], extra current conveyor transconductance amplifier (EXCCTA) [21], differential difference current conveyor (DDCCII) [18], fully differential current conveyor (FDCCII) [15], current differencing buffer amplifier (CDBA) [3], etc. The voltage differencing buffered amplifier (VDBA) is another popular ABB that is very simple in design and versatile in realizing numerous applications [3,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In many analog signal processing applications, an active mixed-mode universal biquadratic filter (MUBF) with input voltages and/or currents, and output voltages and/or currents, is necessarily required. Over the last decade, numerous universal biquad filter realizations in mixed-mode operations based on different active components have already been developed in [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, little effort has been made on the design of DMQO [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The realizations in [ 1 , 2 , 4 , 5 , 6 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 17 , 18 , 19 , 20 , 22 , 23 , 25 , 26 , 29 , 30 , 31 , 33 , 34 , 37 , 39 , 42 , 43 , 44 , 45 , 46 , 47 , 49 , 50 ] need two or more active components. Four or more passive components were used in the circuits described in [ 2 , 3 , 4 , 6 , 8 , 9 , 12 , 13 , 14 , 15 , 16 , …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a multitude of the previously discussed mixed-mode filters [3][4][5][6][7][8]10,12,16,18,22,23,25,27,31,35,36,38,41,42,44,45] employ an excessive number (at least five) of passive components. It has been observed that the realizations of [3][4][5][6][7][8]12,[14][15][16]18,[21][22][23][24]26,27,31,[33][34][35][37][38][39][41][42][43]45,46] still used some floating passive components, whic...…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the realizations of [3][4][5][6][7][8]12,[14][15][16]18,[21][22][23][24]26,27,31,[33][34][35][37][38][39][41][42][43]45,46] still used some floating passive components, which is unfavorable from integrated circuit (IC) implementation viewpoint. To obtain various filtering responses or to change the operating mode, the designs in [5,7,27,32,42] need structural modification with a programmable switching technique. This technique needs to employ some external switches, which practically lead to increasing switching noise.…”
Section: Introductionmentioning
confidence: 99%